Loop-Mediated Isothermal Amplification (LAMP), an innovation in gene amplification: Bridging the gap in molecular diagnostics; a review - Atif Amin, Baig; Wan Rohani, Wan Taib; Rochman, Naim (Indian Society for Education and Environment, 2015)
Loop-Mediated Isothermal Amplification (LAMP), through its uniqueness has provided the world with a powerful molecular diagnostic tool. This innovative gene amplification technique, amplifies nucleic acid at a very rapid pace, maintaining high sensitivity, specificity and efficiency. The most innovative features of LAMP, is the simplicity of its protocol, and overall low cost of application. Other features of LAMP are highlighted in this review, though with few limitations. The demerits include highly technical and cumbersome primer design protocol, and relative scarcity of some materials needed for the technique. The standout features however, ranges from the strand displacement activity of the Bst and Bsm polymerase enzymes, to its ability to amplify gene in an unprocessed samples. The PCR and other several pre-existing techniques, has contributed immensely in disease diagnosis and molecular biology at large. However, their use in molecular diagnostics is mostly limited to highly resourced establishment, leaving the low resourced settings with little or no hope. The cheapness and user-friendliness of LAMP amongst other advantages made it an ideal diagnostic tool that provides solution to the odds of PCR and its likes. The outstanding qualities displayed by LAMP in various researches, has led to several modifications in the technique. Presently several forms of LAMP kits, such as Lyophilized LAMP Kit, electric LAMP device (eLAMP), and combined use of LAMP and Lateral Flow Assay (LFA), are been adopted for diagnosis of many pathogens.